Polarized monolithic white semipolar (20–21) InGaN light-emitting diodes grown on high quality (20–21) GaN/sapphire templates and its application to visible light communication. (January 2020) - Khoury, Michel; Li, Hongjian; Li, Panpan; Chow, Yi Chao; Bonef, Bastien; Zhang, Haojun; Wong, Matthew S.; Pinna, Sergio; Song, Jie; Choi, Joowon; Speck, James S.; Nakamura, Shuji; et al.
Abstract: We demonstrate efficient, polarized and monolithic white semipolar (20–21) InGaN light-emitting diodes (LEDs) grown on high crystal quality 4-inch (20–21) GaN/sapphire template. Materials growth by metal-organic chemical vapor deposition (MOCVD) and characterization by atom probe tomography (APT) were carried out. The fabricated regular 0.1 mm 2 size LEDs show a high electrical performance with an output power of 3.9 mW at 100 mA, an emission spectrum with two peaks located at 445 nm and 565 nm, a CIE point of (0.37, 0.42) and a polarization ratio of 0.30, which make them promising candidates for backlighting in liquid crystal displays (LCDs) application. Moreover, the fabricated square phosphor-free white μLED with size ranging from 20 to 60 μm, exhibit a high 3 dB modulation bandwidth of 660 MHz in the visible light communication (VLC) system, which benefits from the shorter carrier lifetime grown on the semipolar (20–21) plane. To our best knowledge, this is the first demonstration of monolithic white semipolar μLEDs in the VLC application, which can overcome the limitation of the slow frequency response of yellow phosphors converted commercial white LEDs. These results demonstrate the huge potentials to produce high efficiency monolithic white semipolar InGaN LEDs on cost-effective large area sapphire substrates. Graphical abstract: The following figures plots the EL emission spectra for the (20–21) device with the polarizer aligned along [1–210] ( x ' -direction) and [10-1-4] ( y ' -direction), the 3 dB bandwidth measurements results in the VLC system for the fabricated square μLEDs with length varied from 20 to 100 μm, and the reconstructed epitaxial structure is by atom probe tomography (APT). Image 1 Highlights: The first demonstration of efficient polarized monolithic white (20-21) semipoloar LEDs grown on low-cost 4-inch sapphire substrate. The monolithic white semipolar LEDs shows two emission peaks located at 445 nm and 565 nm, with a CIE of (0.37, 0.42). The polarization ratio is measured to be 0.30, which shows a much higher converted efficiency in the LCDs application, as compared to the unpolarized commercial c-plane polar LEDs. The fabricated monolithic white semipolar µLEDs present a high 3dB bandwidth of 660 MHz in the visible light communication system, which can overcome the limitation of the slow response of yellow phosphor converted commercial white LEDs.